Baseline concentrations, spatial distribution and origin of trace elements in marine surface sediments of the northern Antarctic Peninsula - Delhaye, Louise J.; Elskens, Marc; Ricaurte-Villota, Constanza; Cerpa Cornejo, Luis Moroni; Kochzius, Marc (Elsevier, 2023)
Increased human activity in the Antarctic Peninsula combined with accelerated melting of its glaciers highlights the importance of monitoring trace element concentrations. Surface sediment samples were collected around King George Island, Hope Bay and in the Bransfield Strait in February 2020 and were analysed by X-ray fluorescence spectroscopy and inductively coupled plasma mass spectrometry. The methods display a good correlation. Our results show clear distinctions between these regions for selected elements with high local heterogeneities. Hope Bay exhibited lower concentrations of Fe, Mn, Co, V, Zn while most stations in the Bransfield Strait and around King George Island showed moderate to significant enrichment in Cu, As and Cd. Twelve stations presented a moderate ecological risk. The consistency of our values supports a natural rather than anthropogenic origin, possibly related to volcanism and the geology of the area. However, our results suggest an increase in Cr that should be further investigated.